EZH2 Inhibitors Suppress Colorectal Cancer by Regulating Macrophage Polarization in the Tumor Microenvironment - Li, Chen; Song, Jiagui; Guo, Zhengyang; Gong, Yueqing; Zhang, Tengrui; Huang, Jiaqi; Cheng, Rui; Yu, Xiaotong; Li, Yanfang; Chen, Li; Ma, Xiaojuan; Sun, Yan; et al. (Frontiers in Immunology, 2022)
EZH2 inhibitors (EZH2i), a class of small-molecule inhibitors that target EZH2 to exert anti-tumor functions, have just been approved by the US Food and Drug Administration (FDA) in treatment of adults and adolescents with locally advanced or metastatic epithelioid sarcoma. The application of EZH2i in several solid tumors is still in different stages of clinical trials and needs to be further validated. As a key epigenetic regulator, besides its role in controlling the proliferation of tumor cells, EZH2 has been implicated in the regulation of various immune cells including macrophages. But there are still controversial research results at present. Colorectal cancer (CRC) is a common malignant tumor that highly expresses EZH2, which has the third highest incidence and is the second leading cause of cancer-related death worldwide. Studies have shown that the numbers of M2-type tumor-associated macrophages (TAMs) are highly associated with the progression and metastasis of CRC. In the current study, we aim to investigate how EZH2 modulates the polarization of macrophages in the tumor microenvironment (TME) of CRC, and compare the role of two different EZH2 inhibitors, EPZ6438 and GSK126. We applied a 3D culture method to demonstrate that EZH2i did indeed suppress the proliferation of CRC cells in vitro. In vivo, we found that the percentage of CD206+ macrophages of the TME was decreased under the treatment of EPZ6438, but it increased upon GSK126 treatment. Besides, in the co-culture system of macrophages and CRC cells, EPZ6438 led to significant elevation of M1 markers and reduction of M2 markers. Furthermore, mechanistic studies validated by ChIP-qPCR demonstrated that EZH2i inhibit EZH2-mediated H3K27me3 levels on the promoters of STAT3, an essential transcription factor for M1 macrophage polarization. Therefore, our data suggested that EZH2i not only suppress CRC cell proliferation directly, but also regulate macrophage by skewing M2 into effector M1 macrophage to exert a tumor suppressive effect. Moreover, our study provided new insight for better understanding of the role of two kinds of EZH2i: EPZ6438 and GSK126, which may pave the way in treating CRC by targeting cancer cells and immune cells via this epigenetic approach in the future.